Why do mothers never stop grieving for their deceased children? Enduring alterations of brain connectivity and function - Kark, Sarah M.; Adams, Joren G.; Sathishkumar, Mithra; Granger, Steven J.; McMillan, Liv; Baram, Tallie Z.; Yassa, Michael A. (Frontiers in Human Neuroscience, 2022)
A child’s death is a profound loss for mothers and affects hundreds of thousands of women. Mothers report inconsolable and progressive grief that is distinct from depression and impacts daily emotions and functions. The brain mechanisms responsible for this relatively common and profound mental health problem are unclear, hampering its clinical recognition and care. In an initial exploration of this condition, we used resting state functional MRI (fMRI) scans to examine functional connectivity in key circuits, and task-based fMRI to examine brain network activity in grieving mothers in response to pictures of their deceased child and as well as recognizable deceased celebrities and unfamiliar individuals. We compared nine mothers who had lost an adult child and aged-matched control mothers with a living child of a similar age. Additionally, we collected diffusion imaging scans to probe structural connectivity and complemented the imaging studies with neuropsychological assessments. Increased functional activation in Ventral Attention/Salience Networks accompanied by a reduced activation in the medial prefrontal cortex in response to the deceased child’s picture robustly distinguished the grieving mothers from controls. Heightened resting-state functional connectivity between the paraventricular thalamic nucleus (PVT) and the amygdala distinguished the grieving mothers from the controls and correlated with subjective grief severity. Structurally, maternal grief and its severity were associated with alterations in corticolimbic white matter tracts. Finally, grieving mothers performed worse than controls on neuropsychological tests of learning, memory, and executive function, linked with grief severity. Reduced activation in cortical regions inhibiting emotions and changes in the PVT circuitry – a region involved in long-term emotional memories and decision making under conflict – distinguish grieving mothers from controls. Notably, the magnitude of neurobiological changes correlates with the subjective severity of grief. Together, these new discoveries delineate a prevalent and under-recognized mental health syndrome and chart a path for its appreciation and care.